Green-synthesised silver and zinc oxide nanoparticles from stingless bee honey : Morphological characterisation, antimicrobial action, and cytotoxic assessment - Norfarina, Bahari; Norhashila, Hashim; Khalina, Abdan; Abdah, Md Akim; Bernard, Maringgal; Laith, Al-Shdifat (Elsevier Ltd., 2025)
This study investigated the green synthesis of silver nanoparticles (Ag-NPs) and zinc oxide nanoparticles (ZnO-NPs) using an aqueous extract of stingless bee honey (SBH) as a reducing and stabilising agent. The rich compositions of SBH containing flavonoids, phenolics, organic acids, sugars, and enzymes makes the SBH extract an ideal biocompatible precursor for the NPs synthesis. Physicochemical characterisation of the synthesised NPs was performed using UV–Vis spectroscopy, FESEM, TEM, XRD, and FTIR spectroscopy. The results revealed that the Ag-NPs and ZnO-NPs exhibited polydispersity, with size ranges between 25-50 nm and 15–30 nm, respectively. A majority of the NPs possessed a spherical morphology. Furthermore, the study evaluated the antimicrobial activity of the SBH-based NPs against gram-positive (Staphylococcus aureus, ATCC 43300) and gram-negative (Escherichia coli, ATCC 25922) bacteria. The findings demonstrated significantly higher antimicrobial efficacy of the Ag-NPs with a zone of inhibition (ZOI) of 16.91 mm against S. aureus, and 17.43 mm against E. coli compared to the ZnO-NPs which having a ZOI of 13.05 mm and 14.01 mm, respectively. Notably, cytotoxicity assays revealed no adverse effects of the synthesised NPs on normal mouse fibroblast (3T3) and human lung fibroblast (MRC5) cells up to 100 μg/ml of concentration. These findings suggest the potential of SBH-based Ag-NPs and ZnO-NPs as safe and effective antibacterial agents for various applications, including pharmaceuticals, cosmetics, ointments, and lotions.